BUDAYA HUKUM DAN IMPLIKASINYA TERHADAP PEMBANGUNAN HUKUM NASIONAL - Muh. Sudirman Sesse (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2013)
The culture of law is acceptance and resistance on a law event indicating each human behavior on legal problem and event brought in to community. The law can't be only seen from the yuridical perspective, but it must be seen by several perspective according to people and nation development either developed or developing countries. National development is an absolute requirement to improve people life, nation, and state.